Cultural variation in the SES-gender interaction in student achievement - Eriksson, Kimmo; Lindvall, Jannika (Frontiers in Psychology, 2023)
Is the socioeconomic gap in academic achievement larger among boys than girls? Several scholars have proposed such an interaction between socioeconomic status (SES) and gender. Prior empirical studies have yielded mixed evidence, but they have been conducted almost exclusively in Western countries. Here we propose that the SES-gender interaction is stronger in less gender-equal societies. To examine this hypothesis, we estimated the SESgender interaction in 36 countries using data from two international large-scale assessments (PIRLS and TIMSS). The degree of gender equality was measured by the Global Gender Gap Index. The SES-gender interaction correlated with gender equality in the expected way. This finding suggests that cultural factors determine how the socioeconomic achievement gap differs between boys and girls.